Exendin-4 Preserves Blood-Brain Barrier Integrity via Glucagon-Like Peptide 1 Receptor/Activated Protein Kinase-Dependent Nuclear Factor-Kappa B/Matrix Metalloproteinase-9 Inhibition After Subarachnoid Hemorrhage in Rat - Xie, Zhiyi; Enkhjargal, Budbazar; Nathanael, Matei; Wu, Lingyun; Zhu, Qiquan; Zhang, Tongyu; Tang, Jiping; Zhang, John H. (Frontiers in Molecular Neuroscience, 2021)
In this study, we investigated the role of Exendin-4 (Ex-4), a glucagon-like peptide 1 receptor (GLP-1R) agonist, in BBB disruption after subarachnoid hemorrhage (SAH) in rats. The endovascular perforation model of SAH was performed in Sprague-Dawley rats. Ex-4 was intraperitoneally injected 1 hour after SAH induction. To elucidate the underlying molecular mechanism, small interfering ribonucleic acid (siRNA) for GLP-1R and Dorsomorphin, a specific inhibitor of adenosine monophosphate-activated protein kinase (AMPK), were intracerebroventricularly injected 48 hours before induction of SAH correspondingly. Immunohistochemistry results supported GLP-1R expressed on the endothelial cells of microvessels in the brain after SAH. Administration of Ex-4 significantly reduced brain water content and Evans blue extravasation in both hemispheres, which improved neurological scores at 24 hours after SAH. In the mechanism study, Ex-4 treatment significantly increased the expression of GLP-1R, p-AMPK, IκB-α, Occludin, and Claudin-5, while the expression of p-nuclear factor-kappa B (NF-κB) p65, matrix metalloproteinase-9 (MMP-9) and Albumin were significantly decreased. The effects of Ex-4 were reversed by intervention of GLP-1R siRNA or Dorsomorphin, respectively. In conclusion, Ex-4 could preserve the BBB integrity though GLP-1R/AMPK dependent NF-κB/MMP-9 inhibition after SAH, which should be further investigated as a potential therapeutic target in SAH.